2022
DOI: 10.3390/foods11244043
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Consumption Behaviour towards Aquatic Food among Asian Consumers: A Systematic Scoping Review

Abstract: Asia accounts for over 70% of total global aquatic food consumption, but aquatic food consumption behaviours and attitudes among Asian consumers are poorly documented and understood. This paper synthesises literature on factors influencing aquatic food consumption behaviour in Asia and the potential to support transitions toward more sustainable food consumption patterns. We identified 113 studies for inclusion in a scoping review, and identified five clusters of publications: (1) product attributes, availabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 150 publications
0
6
0
Order By: Relevance
“…Further, price reduction and discount percentage can have varying effects in influencing willingness to pay for MSPCED. In line with this finding, price is considered the most crucial factor affecting consumer buying decisions (70)(71)(72) and is still the main barrier to consumers' willingness to buy products close to the expiry date (71). In Denmark, a recent initiative by DanChurchAid focused exclusively on surplus goods, being the first initiative of its kind offering food products that regular supermarkets can no longer sell for reasons such as overdue 'best before' dates or damaged packaging at 30-50% below market prices (73).…”
Section: Discussionmentioning
confidence: 78%
“…Further, price reduction and discount percentage can have varying effects in influencing willingness to pay for MSPCED. In line with this finding, price is considered the most crucial factor affecting consumer buying decisions (70)(71)(72) and is still the main barrier to consumers' willingness to buy products close to the expiry date (71). In Denmark, a recent initiative by DanChurchAid focused exclusively on surplus goods, being the first initiative of its kind offering food products that regular supermarkets can no longer sell for reasons such as overdue 'best before' dates or damaged packaging at 30-50% below market prices (73).…”
Section: Discussionmentioning
confidence: 78%
“…Factors which influence food consumption behavior are complex as they extend beyond hunger or nutrition into personal and socio-cultural dimensions [21,22]. Previous studies have found numerous factors influence the consumption of seafood [23], such as sensory attributes such as freshness or taste [9,24], consumption during childhood [9,10,25], regional variability or place [26], and demographics [27].…”
Section: Consumption Of Seafoodmentioning
confidence: 99%
“…Many studies have focused on how the definition of sustainable fish consumption can be transformed into concrete actions, identifying milestones to promote this behavior [12]. Consumers' attitudes, awareness, preferences, and behaviors as well as factors influencing them have been investigated in many studies [13][14][15][16][17][18][19][20][21]. Other researchers have analyzed the differences between consumers with greater and lesser knowledge of seafood products, showing that the former is more oriented toward sustainable purchasing choices and more diversified consumption of seafood species [22,23].…”
Section: Literature Background 21 Young Generations Toward Sustainabl...mentioning
confidence: 99%